Peran Pendidikan Agama Islam di PAUD dalam Membangun Karakter Moderat Anak Usia Dini: The Role of Islamic Religious Education in PAUD in Building Moderate Character in Early Childhood - Mukhtar Zaini Dahlan (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Early childhood character education is crucial in shaping individuals with tolerant, inclusive, and moderate attitudes, especially in a pluralistic society. One of the instruments that can be used to instill the values ??of religious moderation in children is Islamic Religious Education (PAI), which is implemented in early childhood education institutions (PAUD). This study aims to analyze the role of PAI in building moderate character in early childhood at PAUD SPS Teratai 23 Kencong, focusing on applying religious moderation values, such as tolerance, respect for differences, and cooperation. The method used in this study is a qualitative approach with a case study at PAUD SPS Teratai 23 Kencong, which examines learning activities that integrate the values ??of moderation in children's daily lives. The study results indicate that the PAI program at PAUD SPS Teratai 23 Kencong has succeeded in teaching moderation values ??through various activities involving children's moral, social, and spiritual aspects. However, several challenges are faced, including a lack of parental understanding of diverse moderation, the influence of social media that can introduce extreme views, and differences of opinion among teachers. This study concludes that collaboration between schools, parents, and the community is essential to ensure the consistent implementation of moderation values so that moderation-based education can shape children's characters to be more inclusive and able to live harmoniously in a diverse society.